Biogeography, systematics and evolution of acoustic communication in Eneopterinae crickets - Vicente, Natállia Maria de Freitas (2015)
Eneopterinae is a widely distributed subfamily of crickets, with species described from most Tropical regions of the world. The subfamily has been recently target of evolutionary and ecological studies once they are the only crickets known to use high-frequency calling songs. Two groups of Eneopterinae are showing this innovation in the communication system: Lebinthini distributed in the Pacific region and Eneopterini from the Neotropics. Specifically, this thesis aims to give answers about the biogeography and evolution of acoustic communication of Eneopterinae crickets in South America. We also explore trough different approaches the complex taxonomy of this group. In the first chapter we used a dated phylogeny calibrated with fossils and biogeographical analyses to estimate the origin, how many times Eneopterini colonized South America and the routes toward and from this continent. In the second chapter, we studied the bioacoustics of the Neotropical genera of Eneopterinae crickets. In the third chapter we used DNA and morphology-based approaches to explore species diversity in the cryptic Eneopterini genus Ligypterus. And finally, in the fourth chapter we described a new genus of Eneopterinae, Gnominthus, focusing on general morphology, bioacoustical analyses of the calling song and the description of the mating behavior. This study advances the understanding of the global biogeographical processes that shaped current distribution patterns. Our dating results show that the subfamily is a Gondwanan group, far older than expected and that its diversification dates back to Late Creataceous (ca. 76 Ma). In this context the colonization of the Neoptropics would have occurred twice independently, very early from an Antarctic origin, resulting from the break-up of a Gondwanan fauna, and later by a northern recolonization coming from South-east Asia, likely related with a Holarctic Boreotropical distribution of the species during the Eocene. Our results indicate a boreotropical migration for Eneopterinae, with interesting patterns of recolonization of South America through the Northern hemisphere. Boreotropical migration, is well-studied in plants, for which it is an important explanation for the biogeography, but is not very explored in animals. In the second chapter, we clarified the evolution of high-frequency songs in Neotropical Eneopterinae crickets, showing a scenario of two independent origins for this feature. In the third chapter, the species discovery methods indicated a considerably higher diversity in the cryptic genus Ligypterus, with probably twice more species than we currently know. And finaly in the fourth chapter we described an endemic Eneopterinae genus from Papua New Guinea with a distinct reproductive behavior and high-frequency calling songs. We believe that the perspectives now open by discussion on this thesis have the potential to offer base for further studies regarding this subfamily and crickets in general. The exploration of the use high-frequency communication in other cricket groups is urgent, given the importance of this feature in the evolution and ecological processes in Eneopterinae. The use of DNA based method may clarify other taxonomic complex crickets groups, unveiling the real diversity in Orthoptera.